Proceedings of the International Conference on Social Studies, Globalisation and Technology (ICSSGT 2019) 2020
DOI: 10.2991/assehr.k.200803.028
|View full text |Cite
|
Sign up to set email alerts
|

Aceh Women’s Contribution of Military Affairs During Western Colonialism in Indonesia

Abstract: Aceh has a great history of faces and against colonialism in Indonesia, include women's contributions. The women's history clearly shows women's involvement in politics and military affairs. It is also supported by achievements of a number of tough women who entitled to heroes, such as Cut Nyak Dien, Cut Meutia, and Laksamana Keumalahayati. In the historical record, Aceh is well known to have a strong Moslem principle that roots deeply in the vein of its people. It gave impact to the function of religious lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…As her husband, Teuku Umar received an offer from the Dutch to get positions and facilities, Cut Nyak Dhien suggested refusing and choosing to return to the Aceh troops and fight against the Dutch [51]. According to the findings, it was revealed that Cut Nyak Dhien was an Indonesian heroine with courage, determination, a strong soul, and agility [52]. She did not give up even though she lived in a remote area for 6 years and felt inadequate with a weakened body.…”
Section: Discussionmentioning
confidence: 99%
“…As her husband, Teuku Umar received an offer from the Dutch to get positions and facilities, Cut Nyak Dhien suggested refusing and choosing to return to the Aceh troops and fight against the Dutch [51]. According to the findings, it was revealed that Cut Nyak Dhien was an Indonesian heroine with courage, determination, a strong soul, and agility [52]. She did not give up even though she lived in a remote area for 6 years and felt inadequate with a weakened body.…”
Section: Discussionmentioning
confidence: 99%
“…Tjoet Nyak Dien is one of Indonesia's heroines who fought against the invaders. However, she still understands her duties and functions as a wife and mother (Yuliati et al, 2020). In other words, Tjoet Nyak Dien does not set an example for superiority over men, as is the spirit of Western feminism.…”
Section: Methodsmentioning
confidence: 95%
“…2546(Siahaan et al, -2547. The involvement of women in the jihad to defend the homeland was exemplified by Acehnese heroes such as Cut Nyak Dien (Yuliati et al, 2020) and Cut Mutia (Zahrina, 2021). Meanwhile, NU women were involved in the Battle of Surabaya as a result of national political awareness during the revolutionary period.…”
Section: Political Conditions Of the Revolutionary Periodmentioning
confidence: 99%